2005
DOI: 10.1292/jvms.67.667
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Lactoferrin with an Inflammatory Effect But No Apparent Antibacterial Activity in Mastitic Mammary Gland Secretion

Abstract: ABSTRACT. We have identified various lactoferrin (Lf) molecules in mastitic mammary gland secretions (MGSs), and these Lf molecules were examined for their physiological function in MG. These Lf molecules were isolated by Con A affinity chromatography, and then analyzed by various electrophoresis methods and N-terminal amino acid sequencing. The low Con A affinity Lf was found to have low molecular peptides as compared with the 86 kDa of the high Con A affinity Lf, which is usually detected in healthy MGSs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…In inflammations, including cow mastitis, the level of proteins (lactoferrin and transferrin) binding this element increases significantly, thus reducing its availability (Weinberg 1986, Komine et al 2005, Chaneton et al 2008. In response to environmentally limited access to iron, staphylococci have developed mechanisms enabling them to uptake this relevant constituent, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In inflammations, including cow mastitis, the level of proteins (lactoferrin and transferrin) binding this element increases significantly, thus reducing its availability (Weinberg 1986, Komine et al 2005, Chaneton et al 2008. In response to environmentally limited access to iron, staphylococci have developed mechanisms enabling them to uptake this relevant constituent, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The milk bLf concentration depends on the severity of the infection. The greatest increase in bLf concentration has been seen for acute coliform mastitis, whereas for subclinical mastitis much lower bLf values are detected (25,29). In all studies, great individual variations in bLf concentration between cows have been reported.…”
mentioning
confidence: 85%
“…On the other hand, we found the concanavalin A (Con A) low-affinity Lf molecules in staphylococcal mastitic MGSs during lactation and the early dry period [20]. The Con A low-affinity Lf is a small molecule of 37 kDa, and it shows a decreasing antibacterial effect and chelating of the iron ion [20]. Moreover, Con A low-affinity Lf has inflammatory effects and induces inflammatory cytokines, chemokines, superoxide and leukocyte infiltration into the bovine mammary gland [20].…”
mentioning
confidence: 91%
“…On the other hand, we found the concanavalin A (Con A) low-affinity Lf molecules in staphylococcal mastitic MGSs during lactation and the early dry period [20]. The Con A low-affinity Lf is a small molecule of 37 kDa, and it shows a decreasing antibacterial effect and chelating of the iron ion [20].…”
mentioning
confidence: 99%